(untitled) (Theatrum historiae, 2024)
This article deals with the communication between the bishops of Olomouc Stanislav Thurzo, Jan Dubravius, and Marek Khuen and the bishop’s towns located in the Hukvaldy and Kelč manors. The correspondence was recorded on sheets written down in the chancery of the Bishop of Olomouc which were copied and compiled into the episcopal record book. The article is primarily based on working with this type of source.